Energy Management and Pricing Strategy of Building Cluster Energy System Based on Two-Stage Optimization - Ma, Lifei; Liu, Jizhen; Wang, Qinghua (Frontiers in Energy Research, 2022)
With the application of advanced information and communication technology in building cluster energy system (BCES), energy management based on two-way interaction has become an effective method to improve its operation efficiency. BCES can quickly respond to the mismatch between supply and demand by adjusting flexible load and system operation strategy, which can improve operation reliability and reduce energy cost. This paper proposes an energy management and pricing framework of BCES based on two-Stage optimization method. First, on the basis of profit-seeking modeling of energy service provider (ESP) and building clusters (BCs), a dynamic pricing decision-making framework for energy management in a hierarchical energy market is proposed, which considers both ESP’s energy supply income and BCs’ comprehensive benefit. The dynamic pricing problem is formulated as a discrete finite Markov decision process (MDP), and Q-learning algorithm is adopted to solve the MDP problem. Moreover, an operation optimization model of the BCES based on the obtained optimal price decision is established, and the established model is solved by the alternating direction multiplier method algorithm (ADMM). Through numerical simulation case studies, it is demonstrated that the proposed method can achieve the optimal pricing decision-making closer to the psychological needs of ESP and BCs, and can significantly reduce the cost of BCs and improve the operational efficiency of BCES.